Guía de supervisión técnica independiente de edificaciones de infraestructura educativa (2019)
In accordance with current regulations, the scope, controls and verifications that the independent technical supervision must carry out in the construction of structural and non-structural elements for infrastructure of educational buildings were identified. In addition to the above, the management base of the structure of the technical supervision guide was taken as the application of the project management processes and the areas of knowledge according to the foundations for project management in the PMBok Guide.